2010
DOI: 10.1111/j.1467-789x.2010.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to promote healthy eating habits: evaluation and recommendations

Abstract: Although in several EU Member States many public interventions have been running for the prevention and/or management of obesity and other nutrition-related health conditions, few have yet been formally evaluated. The multidisciplinary team of the EATWELL project will gather benchmark data on healthy eating interventions in EU Member States and review existing information on the effectiveness of interventions using a three-stage procedure (i) Assessment of the intervention's impact on consumer attitudes, consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Unfortunately, this appears to be untrue [115][116][117]. Primary drivers in food selection are taste, convenience and price [118][119][120][121].…”
Section: Is It Possible To Market Cancerpreventive Foods Such As Brocmentioning
confidence: 97%
“…Unfortunately, this appears to be untrue [115][116][117]. Primary drivers in food selection are taste, convenience and price [118][119][120][121].…”
Section: Is It Possible To Market Cancerpreventive Foods Such As Brocmentioning
confidence: 97%
“…Policy makers, scientific researchers, and health-care workers have become increasingly interested in intervention strategies that stimulate healthier and more responsible food-choice behavior [ 8 ], particularly because consuming high quantities of calories through sugar and fat potentially becomes addictive [ 9 , 10 ]. These intervention strategies, when effective, can reduce the burden of obesity and related non-communicable diseases such as diabetes, cancers, and cardiovascular diseases [ 11 ]. Intervention strategies come in many shapes and forms, varying from public health campaigns to a ban of advertising unhealthy foods to children.…”
Section: Introductionmentioning
confidence: 99%
“…Within the food domain, a number of surveys have found that beliefs about the causes of obesity affect support for obesity prevention policies [16-18]. However, a structured insight into consumers’ perceptions of interventions is lacking [19]. …”
Section: Introductionmentioning
confidence: 99%